Memahami kode etik guru sebagai panduan perilaku bagi profesi pendidik di sekolah - Adzani, Wanasa Rahmat Akbar (Maliki Interdisciplinary Journal, 2024)
The teacher's code of ethics is a code of conduct that regulates the responsibilities and professional actions of teachers. However, its implementation still faces challenges such as a lack of understanding, a less conducive work environment, and a weak monitoring and enforcement system. Comprehensive efforts are needed to improve implementation of the code of ethics, including outreach, training, strengthening monitoring and sanction systems, as well as government and community support. Building an organizational culture that is positive, has integrity and supports the application of ethical values is also the key to creating a conducive environment. Active involvement of all stakeholders, including teachers, students, parents and the community, is needed in this effort. With coordinated and sustained efforts, it is hoped that implementation of the code of ethics can be improved, improving the quality of education and maintaining the dignity of the teaching profession.